Pendampingan Sekolah Berwawasan Lingkungan dan Mitigasi Bencana Berbasis Virtual Reality di SD Muhammadiyah 9 Bahari Surabaya: Assistance for Environmentally Friendly School Programs and Virtual Reality-Based Disaster Mitigation at SD Muhammadiyah 9 Bahari Surabaya - Sumara, Retno; Putra, Andhika Cahyono; Firman, Firman; Suharti, Peni (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The geographical location of SD Muhammadiyah 9 Kenjeran Surabaya is on the coast which makes it face the risk of flooding and serious environmental health challenges, which require further intervention. The rampant dumping of rubbish in the surrounding environment makes the school feel anxious because it could result in flood disasters and environmental damage, as well as a decline in the community's health status. This service aims to provide counseling and outreach to students using the VR-DISASTER learning media at SD Muhammadiyah 9 Bahari Kenjeran Surabaya. Methods for implementing activities, in the form of lectures, discussions, and practice. This 1-day training was effective in increasing knowledge and changing participants' attitudes. Proven by the Pre-test results show that the majority of students have a low level of knowledge, both regarding environmental health (68.57%) and disaster mitigation (91.43%). However, after being provided with counseling and socialization using VR-DISASTER, the post-test results showed a significant increase with 100% of students having high knowledge about environmental health and 82.86% of students with a level of disaster mitigation knowledge which also increased. Thus, it is hoped that the level of knowledge possessed by students can increase awareness and preparedness for disasters that could occur at SD Muhammadiyah 9 Bahari Surabaya.